2021
DOI: 10.1021/acs.cgd.1c00945
|View full text |Cite
|
Sign up to set email alerts
|

Hexagonal Ge Grown by Molecular Beam Epitaxy on Self-Assisted GaAs Nanowires

Abstract: Hexagonal group IV materials like silicon and germanium are expected to display remarkable optoelectronic properties for future development of photonic technologies. However, the fabrication of hexagonal group IV semiconductors within the vapor-liquid-solid method has been obtained using gold as a catalyst thus far. In this letter, we show the synthesis of hexagonal Ge on self-assisted GaAs nanowires using molecular beam epitaxy. With an accurate tuning of the Ga and As molecular beam flux we selected the crys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Full MBE growth of stemless InSb nanowires could also be explored, using an As Cracker as the As source to initiate the InSb nanowire growth, and subsequently closing the As shutter to continue the growth of pure InSb nanowires from indium and antimony elemental sources. Nonetheless, it might still be challenging to completely eliminate the presence of As carry-over with this method, as reported in a prior study [45]. Alternatively, developing InSb platforms with inclined {111}B facets such as trenches or ridges, similar to those developed on InP [19,25,68] or InAs [21,65], could eliminate the need for As or stems to initiate InSb nanowire nucleation [24].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Full MBE growth of stemless InSb nanowires could also be explored, using an As Cracker as the As source to initiate the InSb nanowire growth, and subsequently closing the As shutter to continue the growth of pure InSb nanowires from indium and antimony elemental sources. Nonetheless, it might still be challenging to completely eliminate the presence of As carry-over with this method, as reported in a prior study [45]. Alternatively, developing InSb platforms with inclined {111}B facets such as trenches or ridges, similar to those developed on InP [19,25,68] or InAs [21,65], could eliminate the need for As or stems to initiate InSb nanowire nucleation [24].…”
Section: Discussionmentioning
confidence: 94%
“…However, we have evidence that strain due to lattice mismatch is fully relaxed at the InP-InSb nanowire interface (see figures S12(a)-(c)). A second hypothesis for the bending behavior could be the use of As during heat up, which might lead to the known 'carry-over' effect [41][42][43][44][45]. Arsenic can stick to the internal parts of the growth chamber and outgas at high temperatures during all the subsequent growth steps, thus being unintentionally incorporated into the growing nanowires and form an InAs x Sb 1−x alloy.…”
Section: Resultsmentioning
confidence: 99%
“…GaAs, due to its direct bandgap and its high carrier mobility, is a promising material for solar energy harvesting with photovoltaics [Vettori et al 2019a] or photoelectrodes [Hu et al 2013, Cui et al 2021, the NW geometry leading to an efficient light trapping. More recently it was demonstrated GaAs NWs can be used as templates for the growth of hexagonal Germanium [Fadaly et al 2020, Dudko et al 2022. However, the maximal reported length of GaAs NWs grown by MBE, at the best of our knowledge, is about 25 μm [Braakman et al 2014] and typical growth time rarely exceeds 2 h [Zhou et al 2017].…”
Section: Introductionmentioning
confidence: 90%
“…In addition, it has been found that wurtzite GaAs is a suitable template to grow 2H-Ge and Ge-based nanomaterials due to the small lattice mismatch between the wurtzite GaAs and 2H-Ge. For example, Ge-rich 2H-Si 1– x Ge x /GaAs core-shell structures can be successfully prepared using wurtzite GaAs nanowires as templates (Figure f–i). , It was also observed that 2H-Ge can be formed on the GaAs template. , …”
Section: Phase Engineering In Elemental Semimetal and Nonmetal Nanoma...mentioning
confidence: 98%
“…221,222 It was also observed that 2H-Ge can be formed on the GaAs template. 221,223 3.1.3. Solution-Based Synthesis.…”
Section: Templated Synthesismentioning
confidence: 99%